Consumptive water use in the critical period as predictor of grain yield of bread wheat, durum wheat and triticale in the pampean semiarid region (Semiárida, 2018)
Bread wheat is the most important winter crop in the Pampean semiarid region. Durum wheat and grain triticale have not been commercially grown in that region in spite of their background of good performances in semiarid environments. Bread wheat yields observed in the region show a high interannual variability (989 to 2664 kg.ha-1). The Fischer photothermal quotient (PTQ) during the critical period (CP) is a simple indicator of grain yield potential, but loses accuracy for conditions of environmental stress. Some evidences indicate that adding the variable consumptive water use (CWU) into the same prediction equation together with PTQ could improve the explanation of grain yield observed in the region. Field tests were performed in the Agronomy Faculty of the Universidad Nacional de La Pampa (36º 46' S and 64º 17' W; 210 m above sea level) on an Entic Haplustoll soil. Measured CWU showed a significant positive correlation with grain yield. An additional yield of 1175 kg.ha-1 was observed per every unit (mm.d-1) of CWU. The degree of explanation of grain yield was not improved when PTQ and CWU were used together in the same prediction equation. It is concluded that, during the CP, grain production of winter annual crops in the Pampean semiarid region can be adequately predicted by the variable CWU without using PTQ.
Keywords: Wheat; Consumptive use; Photo-thermal quotient